UPAYA MENINGKATKAN KETERAMPILAN MENULIS KARANGAN SISWA KELAS IV SEKOLAH DASAR DENGAN MENGGUNAKAN MEDIA GAMBAR BERSERI - Fajar Setiawan; Lilik Binti Mirnawati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
he purpose of this research is to improve the writing skill of fourth grade students of elementary school by using the media of series image. The subjects of this research are fourth grade students of SDN Randegansari Driyorejo Gresik academic year 2016/2017. This type of research is a classroom action research conducted through four stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. Techniques of collecting data by means of observation and tests, then the instrument used in the form of a sheet of onservasi implementation of learning, a matter of test results writing skills writing essay, and sheet of field notes. The result of the research proves if the media of the series image can make the result of student's writing skill learning skill have increased by classical, from 74% in cycle I to 88% in cycle II In addition, the implementation oflearning also experienced continuous improvement, and the constraints encountered can be overcome well. That way, it can be drawn conclusion if the student's writing skills can beimproved using the media image series Keywords: Writing Authorship, Glowing Pictures